2021
DOI: 10.1109/access.2021.3083554
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning–Based Mobility Robustness Optimization Under Dynamic Cellular Networks

Abstract: In this paper, we propose a machine learning−based mobility robustness optimization algorithm to optimize handover parameters for seamless mobility under dynamic small-cell networks. Small cells can be arbitrarily deployed, portable, and turned on and off to fulfill wireless traffic demands or energy efficiency. As a result, the small-cell network topology dynamically varies challenging network optimization, especially handover optimization. Previous studies have only considered dynamics due to user mobility i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…One of the objectives is to observe multiple HO events with associated parameters, use this information to train its machine learning model, and try to identify sets of parameters that lead to successful HOs and sets of parameters that lead to unintended events. Some recent literatures have shown that machine learning‐based mobility robustness optimization can improve the user satisfaction rate and increase network performance significantly by optimizing HO parameters [51,52]. We anticipate that the mobility optimization enhanced by the use of machine learning can find the optimal HO parameters to maximize the MASE solving the various complex trade‐offs.…”
Section: Discussionmentioning
confidence: 94%
“…One of the objectives is to observe multiple HO events with associated parameters, use this information to train its machine learning model, and try to identify sets of parameters that lead to successful HOs and sets of parameters that lead to unintended events. Some recent literatures have shown that machine learning‐based mobility robustness optimization can improve the user satisfaction rate and increase network performance significantly by optimizing HO parameters [51,52]. We anticipate that the mobility optimization enhanced by the use of machine learning can find the optimal HO parameters to maximize the MASE solving the various complex trade‐offs.…”
Section: Discussionmentioning
confidence: 94%
“…In [40], a distributed reinforcement learning was proposed to adapt the UE mobility along with proposing ML-based algorithm (i.e., transfer learning based algorithm) for a dynamic network topology adaption. The main objective of the proposed algorithm is to optimize the HOM, TTT and CIO over a dynamic small BSs to minimize the ratio of the HOF and HOPP.…”
Section: Mro Using Reinforcement Learningmentioning
confidence: 99%
“…Article [31] applied random walk mobility model. Manhattan grid mobility model and random way point mobility model are presented in [40], the random way point mobility model used in pedestrian environment at user speed of 5 km/hr. Constant velocity mobility model is introduced in [41].…”
Section: B Mobility Models For Mro Functionmentioning
confidence: 99%
See 2 more Smart Citations